2018
DOI: 10.1007/s11307-018-1202-2
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Dedicated Preclinical PET/CT System for the Assessment of Mineralization Process in a Mouse Model of Atherosclerosis

Abstract: Optimizing reconstruction parameters significantly impacted on the assessment of mineralization process in a preclinical model of accelerated atherosclerosis using Na[F]F PET. In addition, improving the CT resolution was associated with a dramatic radiation dose increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…fluoride into mineralizing tissues [19][20][21][22][23] . These techniques allow for high resolution threedimensional imaging but are limited by the availability of specialized equipment, carry additional safety considerations, and require development of conjugated or radioactive reporters.…”
Section: Previous Researchers Have Used Single-photon Emission Comput...mentioning
confidence: 99%
“…fluoride into mineralizing tissues [19][20][21][22][23] . These techniques allow for high resolution threedimensional imaging but are limited by the availability of specialized equipment, carry additional safety considerations, and require development of conjugated or radioactive reporters.…”
Section: Previous Researchers Have Used Single-photon Emission Comput...mentioning
confidence: 99%
“…Key aspects for the critical appraisal of the applicability of PET are summarized with regards to the applicability of PET in vivo and ex vivo, the location and size of VC identifiable by PET, the repeatability of analysis in longitudinal studies, the compatibility with additional methods, and the personal and technical expanse. The exemplary workflow presented is based on the publications of [ 140 , 141 , 142 , 143 , 144 , 145 ]. …”
Section: Methods For the Detection Of Vascular Calcification In Rodentsmentioning
confidence: 99%
“…For imaging and quantification of calcification, the establishment of reconstruction parameters is decisive. A study evaluating PET performance found a significant impact on the assessment of the mineralization process by optimizing the reconstitution parameters in uremic and non-uremic rats [141]. In ApoE −/− mice on a high cholesterol diet, a 18 F-NaF PET/CT scan was conducted in vivo in isoflurane-anaesthetized mice with an intraperitoneal tracer injection, as well as ex vivo and calcification were found to progress over the time of high cholesterol feeding with results consistent between in vivo and ex vivo settings [142].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…High spatial resolution is critical in preclinical positron emission tomography (PET) imaging where the ultimate goal would be to obtain an image definition in small animal models similar to that obtained in humans with clinical imaging. Since mice are three orders of magnitude smaller than humans, submillimetric (or submicroliter) spatial resolution is essential to discriminate small regions involved in tumor heterogeneity (Buvat et al 2015), inflammation processes (Rucher et al 2018), neurodegenerative disease progression (Dubois et al 2016) or cardiac gated studies (Croteau et al 2003).…”
Section: Introductionmentioning
confidence: 99%